Advances in prognostic markers for colorectal cancer*. (3rd April 2019) - Duan, Lili; Yang, Wanli; Wang, Xiaoqian; Zhou, Wei; Zhang, Yujie; Liu, Jinqiang; Zhang, Hongwei; Zhao, Qingchuan; Hong, Liu; Fan, Daiming
ABSTRACT: Introduction : Colorectal cancer (CRC) is one of the most common malignant tumors worldwide and contributes significantly to cancer-related deaths. Since CRC is largely asymptomatic until alarm features develop to advanced stages, the incidence and mortality rate of CRC is relatively high and increases year by year. Areas covered : This review mainly summarizes the recent advances of genetic, epigenetic, and proteomic molecular markers that may be used to predict the prognosis of CRC. Moreover, we made an introduction to immune biomarkers and emerging microbial biomarkers. We also discussed the recent movement of molecular pathological epidemiology (MPE) in the context of prognostic biomarkers. Finally, we discussed the pros and cons of various biomarkers for improving prognostic judgment. Expert opinion : A great number of molecular targets have been identified as prognostic markers for CRC. However, because of some limitations, the efficiency of these biomarkers is restricted in clinical application. Combining a panel of several approaches may present a promising alternative tool for clinical practice. Further large-scale clinical trials are required to validate the prognostic value of these biomarkers in clinical use.